Penyidikan Dugaan Tindak Pidana dalam Penagihan Hutang Oleh Debt Collector di Wilayah Hukum Kepolisian Daerah Bali - I Dewa Made Wira Adinata; Dewi Bunga (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Debt collection is part of financial services activities regulated by various legal umbrellas to guarantee the protection of the rights of creditors and debtors. However, in practice, collection is often carried out through criminal acts such as threats, extortion, and violence. This study aims to determine the process and obstacles in the investigation of alleged criminal acts of debt collection by debt collectors in the Bali Regional Police area. This research is a descriptive study using empirical legal methods. Data were obtained through semi-structured interviews and observations at the Bali Regional Police's Criminal Investigation Unit. The results indicate that the investigation process of alleged criminal acts in debt collection by debt collectors in the Bali Regional Police area is carried out systematically in three stages. The stages are carried out starting from receiving reports, investigations, examination of witnesses and suspects, collection of evidence, until the determination of suspects in accordance with the provisions of Article 7 number 1 of Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP). Based on the results of the analysis, it was found that there is a conformity between investigative practices in the field with applicable legal provisions and investigative theories in criminal procedure law. However, in practice, several factors hinder the investigation process, such as the absence of witnesses or complainants during questioning and a lack of public understanding of the procedures. Investigators have undertaken two measures, in accordance with Article 22, point 1, of Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP): sending summonses and conducting home visits. Based on the research findings, it can be concluded that the investigation into criminal acts committed by debt collectors within the jurisdiction of the Bali Regional Police Criminal Investigation Directorate has been conducted in accordance with applicable theory and legal provisions.